Radiosensitivity in patients suffering from chronic kidney disease. (February 2015) - Rodríguez-Ribera, Lara; Corredor, Zuray; Sandoval, Silvia B.; Coll, Elisabet; Silva, Irene; Diaz, Juan Manuel; Ballarin, José; Marcos, Ricard; Pastor, Susana
Abstract: Purpose : Patients suffering from chronic kidney disease (CKD) exhibit a high incidence of cancer, as well as high levels of genetic damage. We hypothesized that these patients show genomic instability detected as an increased chromosomal radiosensitivity in front of the genetic damage induced by ionizing radiation. Material and methods : The background levels of genetic damage and the net genetic damage after in vitro irradiation with 0.5 Gy were analyzed using the micronucleus (MN) assay in peripheral blood lymphocytes. A total number of 552 individuals (179 controls and 373 CKD patients) were included in the study. Results : The net radiation-induced genetic damage was significantly higher in CKD patients than in controls; but no differences between those patients submitted to hemodialysis and those in pre-dialytic stages were detected. A positive correlation was observed between basal and net micronucleus frequencies in CKD patients what would indicate an underlying genetic background modulating DNA damage levels. Conclusions : Our results indicate that CKD patients present genomic instability, measured as an increased chromosomal radiosensitivity in front of ionizing radiation.